Nitrogen use efficiency in cotton: Challenges and opportunities against environmental constraints - Shah, Adnan Noor; Javed, Talha; Singhal, Rajesh Kumar; Shabbir, Rubab; Wang, Depeng; Hussain, Sadam; Anuragi, Hirdayesh; Jinger, Dinesh; Pandey, Himanshu; Abdelsalam, Nader R.; Ghareeb, Rehab Y.; Jaremko, Mariusz (Frontiers in Plant Science, 2022)
Nitrogen is an essential nutrient for crop plants, its deficiency causes stagnant growth and yield in cotton. To enhance cotton productivity, farmers largely rely on the excessive application of N which causes, sometimes, a reduction in lint yield and quality and N use efficiency (NUE). Thus, enhancing NUE in cotton is one of the major concerns to reduce the environmental risk and increase farm profitability. NUE is significantly influenced by different management practices including the source, rate, time, and method of N application, crop growth stage, and genotypes. Different N formulations such as slow and controlled released fertilizers are reported to enhance N uptake which ultimately increases NUE. Increasing N rates are reported to increase the cotton yield, but excessive rates potentially reduced the yield, depending on the soil and environmental conditions. In this study, we comprehensively review different factors, including agronomic- and environmental-related constraints, affecting N uptake, its accumulation in plants, and ultimately NUE in cotton. Furthermore, we also discuss various agronomic and molecular approaches to enhance plant efficiency for N uptake and its utilization in cotton.